A Joint Soil‐Vegetation‐Atmospheric Water Tagging Procedure With WRF‐Hydro: Implementation and Application to the Case of Precipitation Partitioning in the Upper Danube River Basin. Issue 7 (30th July 2019) - Arnault, Joël; Wei, Jianhui; Rummler, Thomas; Fersch, Benjamin; Zhang, Zhenyu; Jung, Gerlinde; Wagner, Sven; Kunstmann, Harald
Abstract: Atmospheric models such as the Weather Research and Forecasting (WRF) model provide a tool to evaluate the behavior of regional hydrological cycle components, including precipitation, evapotranspiration, soil water storage, and runoff. Recent model developments have focused on coupled atmospheric‐hydrological modeling systems, such as WRF‐Hydro, in order to account for subsurface, overland, and river flow and potentially improve the representation of land‐atmosphere interactions. The aim of this study is to investigate the contribution of lateral terrestrial water flow to the regional hydrological cycle, with the help of a joint soil‐vegetation‐atmospheric water tagging procedure newly developed in the so‐called WRF‐tag and WRF‐Hydro‐tag models. An application of both models for the high precipitation event on 15 August 2008 in the German and Austrian parts of the upper Danube river basin (94, 100 km 2 ) is presented. The precipitation that fell in the basin during this event is considered as a water source, is tagged, and subsequently tracked for a 40‐month period until December 2011. At the end of the study period, in both simulations, approximately 57% of the tagged water has run off, while 41% has evaporated back to the atmosphere, including 2% that has recycled in the upper Danube river basin as precipitation. In WRF‐Hydro‐tag, the surface evaporation of tagged water is slightly enhanced by surface flow infiltration and slightly reduced by subsurface lateral water flow in areas with low topography gradients. This affects the source precipitation recycling only in a negligible amount. Key Points: A joint soil‐vegetation‐atmospheric water tagging procedure is incorporated into the WRF and WRF‐Hydro models Lateral terrestrial water flow slightly modifies the partitioning of precipitation event water among terrestrial‐atmospheric compartments The procedure can be adapted to track water from any water compartment in WRF‐Hydro, which widens the range of future application studies